Dynamics of Photo‐Induced Surface Oxygen Vacancies in Metal‐Oxide Semiconductors Studied Under Ambient Conditions. Issue 22 (30th September 2019) - Glass, Daniel; Cortés, Emiliano; Ben‐Jaber, Sultan; Brick, Thomas; Peveler, William J.; Blackman, Christopher S.; Howle, Christopher R.; Quesada‐Cabrera, Raul; Parkin, Ivan P.; Maier, Stefan A.
Abstract: Surface‐enhanced Raman spectroscopy (SERS) is a powerful analytical technique commonly used in the detection of traces of organic molecules. The mechanism of SERS is of a dual nature, with Raman scattering enhancements due to a combination of electromagnetic (EM) and chemical contributions. In conventional SERS, the EM component is largely responsible for the enhancement, with the chemical contribution playing a less significant role. An alternative technique, called photo‐induced enhanced Raman spectroscopy (PIERS) has been recently developed, using a photo‐activated semiconductor substrate to give additional chemical enhancement of Raman bands over traditional SERS. This enhancement is assigned to surface oxygen vacancies ( V o ) formed upon pre‐irradiation of the substrate. In this work, the exceptional chemical contribution in PIERS allows for the evaluation of atomic V o dynamics in metal oxide surfaces. This technique is applied to study the formation and healing rates of surface‐active V o in archetypical metal‐oxide semiconductors, namely, TiO2, WO3, and ZnO. Contrary to conventional analytical tools, PIERS provides intuitive and valuable information about surface stability of atomic defects at ambient pressure and under operando conditions, which has important implications in a wide range of applications including catalysis and energy storage materials. Abstract : Oxygen vacancy defects play significant roles in altering the overall reactivity and functionality of metal oxides affecting both bulk and surface properties, even at very low concentrations. Surface vacancies have only previously been studied under far from operando conditions. Through photo‐induced enhanced Raman spectroscopy, a method to indirectly track the dynamics of photo‐induced surface oxygen vacancies is presented.